Reviews (New blackfriars, 1968)
MORE NEW TESTAMENT STUDIES, by C. H. Dodd THE TRUTH OF THE BIBLE, by Oswald Loretz UNDERSTANDING BIBLICAL RESEARCH, by Luis Alonso Schökel, S.J. COVENANT AND CREATION, by Piet Schoonenberg, S.J. AN INTRODUCTION TO THE THEOLOGY OF RUDOLF BULTMANN, by Walter Schmithals IN PURSUIT OF DIETRICH BONHOEFFER, by William Kuhns ON THE BOUNDARY, by Paul Tillich PERSPECTIVES ON NINETEENTH AND TWENTIETH CENTURY PROTESTANT THEOLOGY, by Paul Tillich KIERKEGAARD ON CHRIST AND CHRISTIAN COHERENCE, by Paul Sponheim THE STRUCTURE OF CHRISTIAN EXISTENCE, by John B. Cobb EXPERIENCE OF LITURGY, edited by Oliver and lanthe Pratt LE TEMPS DE LA LITURGIE EST-IL PASSE?, by Andre Aubry VIE LITURGIQUE ET VIE SOCIALE, by A. Hamman MYSELF AND OTHERS: A STUDY IN OUR KNOWLEDGE OF MINDS, by Don Locke THE ETHICS OF PUNISHMENT, by Sir Walter Moberly RACE, JOBS, AND THE LAW IN BRITAIN, by Bob Hepple SOCIAL CLASS, LANGUAGE AND EDUCATION, by Denis Lawton THE ELEVENTH HOUR. EXPLOSION OF A CHURCH, by François Houtart, edited by Mary Ann Chouteau, with an introduction by Harvey Cox THEORY AND PRACTICE OF FAMILY PSYCHIATRY, by John G. Howells